Evaluasi Pengembangan Pembelajaran Biologi Berbasis Media E- Learning pada Mahasiswa Tadris Biologi 3 Semester VI Universitas Islam Negeri Sumatera Utara - Oktariani, Puput; Pasaribu, Kana Furkonah; Khairunnisa, Azra; Amina, Siti; Sari, Sri Melina; Adiesty, Zahwa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The word learning is not far from a word, namely evaluation, as time goes on, and with the sophistication of existing technology, it creates various kinds of media in the application of learning. E-Learning is the answer to all the sophistication that exists at this time. Where learning methods using current technology are urgently needed because of advances in technology in each learning place or school or college. This research uses the Research and Development method. The purpose of this study is to determine the development of E-Learning media-based learning. The results of the data that the researcher will obtain are the responses of Tadris Biology 3rd Semester VI UINSU Students. Hopefully what is expected with this article can be an alternative choice or reference in conducting a study. Keywords: Development of learning and E-Learning